2013
DOI: 10.3354/dao02659
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent prevalence of anti-Brucella antibodies in hooded seals Cystophora cristata

Abstract: Investigations of hooded seals Cystophora cristata have revealed high prevalences of Brucella-positive seals in the reduced Northeast Atlantic stock, compared to the increasing Northwest Atlantic stock. This study evaluated the relation between Brucella-serostatus in seals in the Northeast Atlantic stock and age, sex, body condition and reproduction. Bacteriology documented which animals and organs were B. pinnipedialis positive. No relationship was observed between Brucella-serostatus and body condition or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 54 publications
9
30
0
Order By: Relevance
“…2). This result is very similar to that in a previous study of hooded seals (Cystophora cristata) in the north Atlantic population, which found that pups (<1 month old) had a lower percentage of seropositivity (2.5%) than yearlings (35.3%) (28). A similar agedependent pattern of anti-Brucella antibodies has also been reported for eastern Pacific harbor seals (P. vitulina richardsi) (29).…”
Section: Discussionsupporting
confidence: 90%
“…2). This result is very similar to that in a previous study of hooded seals (Cystophora cristata) in the north Atlantic population, which found that pups (<1 month old) had a lower percentage of seropositivity (2.5%) than yearlings (35.3%) (28). A similar agedependent pattern of anti-Brucella antibodies has also been reported for eastern Pacific harbor seals (P. vitulina richardsi) (29).…”
Section: Discussionsupporting
confidence: 90%
“…It seems likely that much of this occurs within the first few months at-sea: weaned pups have around a month to develop an effective foraging strategy before terminal starvation occurs (Bennett, Speakman, Moss, Pomeroy, & Fedak, 2007). There is evidence that juvenile seals may be more susceptaible to disease than adults, however, as energy is directed to growth at the expense of their immune system (Nymo et al, 2013). Thus, although such individuals may face a degree of competitive exclusion from the most profitable foraging patches (Breed, Bowen, & Leonard, 2013), there is no evidence that starvation-induced mortality would be higher in juveniles (aged 1-5 years) compared with adults (aged 6+ years).…”
Section: Model Adequacy and Extensionsmentioning
confidence: 99%
“…Recently, two independent studies suggest that hooded seals are not the definitive host of B. pinnipedialis (67,89). Indeed, gross pathology associated with B. pinnipedialis infection has not been described in seals and vertical transmission is not likely to occur, since B. pinnipedialis has never been isolated from females of reproductive age.…”
Section: Brucella Ceti and Brucella Pinnipedialis Infections In Marinmentioning
confidence: 99%